Mapping of technogenic contamination of environment of Janajol fields (Journal of Geography and Environmental Management, 2019)
By ecology of environment of Janajolfields there are ecological positions of function of atmosphere,hydrosphere and sial, idest for the estimation of ecology the explored area it is necessary to define thelevel of contamination of the adopted spheres and by their intercommunication interse. Contaminationsof environment of deposit Janajol it is related to the next basic sources: production of oil; a quarry Atash;aplace to bury a purified drilling mud.